PENERAPAN MEDIA ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS I SD NEGERI 36 HALMAHERA SELATAN PADA TEMA I SUBTEMA 2 ANGGOTA TUBUHKU - Retina Munir; Kodrat Hi Karim; Eko Purnomo (PEDAGOGIK, 2022)
This research was conducted with the aim of (1) knowing the learning process of the first graders of SDNegeri 36 South Halmahera using animation learning (2) knowing the improvement of the learningoutcomes of first graders of SD Negeri 36 South Halmahera using animation learning media. The type ofthis research is Classroom Action Research (CAR) which consists of 3 stages, namely (1) Planning, (2)Implementation and Observation, (3) Reflection. The research subjects were first grade students with 14students consisting of 9 female students and 5 male students. Data collection techniques in this study areobservation, documentation and tests. The data analysis technique in the study was carried out in threestages, namely to determine the mastery of student learning outcomes individually, to determine the masteryof student learning outcomes classically and to calculate the percentage of student and teacher activityresults.Based on the results of research from applying animation learning media in improving student learningoutcomes in the first cycle of students who completed as many as 9 students or 64.28% while those whohad not completed as many as 5 students or 35.71% of the 14 students who took part in the learning processin class with a total of the first cycle is 62.71%. this shows that the application of animated learning mediato improve student learning outcomes in Class I SD Negeri 36 South Halmahera. has not succeeded. Whilein the second cycle there were 12 students who completed or 85.71% while those who did not completewere 2 students or 14.28% of the 14 students who took part in the learning process in class with an averagenumber of cycle II was 80.28%. Thus, it can be concluded that the application of animated learning mediacan improve the learning outcomes of first grade students at SD Negeri 36 South Halmahera